2022
DOI: 10.1111/nmo.14358
|View full text |Cite
|
Sign up to set email alerts
|

Effect of percutaneous electrical nerve field stimulation on mechanosensitivity, sleep, and psychological comorbidities in adolescents with functional abdominal pain disorders

Abstract: Background Percutaneous electrical nerve field stimulation (PENFS) improves symptoms in adolescents with functional abdominal pain disorders (FAPDs). However, little is known about its impact on sleep and psychological functioning. We evaluated the effects of PENFS on resting and evoked pain and nausea, sleep and psychological functioning, and long‐term outcomes. Methods Patient ages 11–19 years with FAPD requiring PENFS as standard care were recruited. Evoked pain was elicited by a Water Load Symptom Provocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 67 publications
(167 reference statements)
1
28
0
2
Order By: Relevance
“…1 -und Kontrolle), Stimulationsparameter, Behandlungsdauer, primäre und sekundäre Ergebnisse sowie beobachtete unerwünschte Ereignisse. [30,40,41,49,53,64,69], n = 154), Migräne (4 Studien [24,39,70,84], n = 133), Rückenschmerz (4 Studien [39,65,66,71], n = 192), rheumatoide Arthritis (RA)/Osteoarthritis (2 Studien [17,46]; n = 45), Fibromyalgie/ systemischer Lupus Erythematodes (SLE) (3 Studien [5,43,79], n = 51), Chemotherapie-induzierte periphere Neuropathie (1 Studie [62]; n = 58), unspezifischer chronischer Schmerz (1 Studie [30], n = 3). Von diesen waren 9 Studien [5,40,41,43,65,66,69,70,84] Schmerz auf einer Visuellen Analogskala (VAS) oder Numerischen Rating-Skala (NRS), psychisches Wohlbefinden und Verträglichkeit/Sicherheit der Stimulation waren die häufigsten primären und sekundären Endpunkte.…”
Section: Materials Und Methodenunclassified
“…1 -und Kontrolle), Stimulationsparameter, Behandlungsdauer, primäre und sekundäre Ergebnisse sowie beobachtete unerwünschte Ereignisse. [30,40,41,49,53,64,69], n = 154), Migräne (4 Studien [24,39,70,84], n = 133), Rückenschmerz (4 Studien [39,65,66,71], n = 192), rheumatoide Arthritis (RA)/Osteoarthritis (2 Studien [17,46]; n = 45), Fibromyalgie/ systemischer Lupus Erythematodes (SLE) (3 Studien [5,43,79], n = 51), Chemotherapie-induzierte periphere Neuropathie (1 Studie [62]; n = 58), unspezifischer chronischer Schmerz (1 Studie [30], n = 3). Von diesen waren 9 Studien [5,40,41,43,65,66,69,70,84] Schmerz auf einer Visuellen Analogskala (VAS) oder Numerischen Rating-Skala (NRS), psychisches Wohlbefinden und Verträglichkeit/Sicherheit der Stimulation waren die häufigsten primären und sekundären Endpunkte.…”
Section: Materials Und Methodenunclassified
“…The safety profile of taVNS is excellent as none of these studies reported side effects. paVNS via 2 mm needle electrodes was reported to improve abdominal pain in adolescents with FGIDs (60 patients with active treatment and 55 with sham treatment), [9] resting and evoked pain in 20 adolescents with functional abdominal pain disorders, [10] and symptoms of IBS in 50 adolescents with IBS. [11] In these studies, the therapy was delivered as follows.…”
Section: Journal Of Translational Internal Medicine / Oct-dec 2022 / ...mentioning
confidence: 99%
“…Advantages Disadvantages taVNS [6][7][8] Auricular vagus nerve via surface electrodes 1-100 Hz FD, IBS Self-administered; home based Daily placement of electrodes paVNS [9][10][11] Auricular vagus nerve via needles 1-100 Hz Pediatric abdominal pain, IBS Device attached to the ear Needle penetration; long stimulation duration tcVNS [12][13] Cervical vagus nerve via surface electrodes 5 kHz Gastroparesis Short study duration (a few minutes)…”
Section: Diseases Being Treatedmentioning
confidence: 99%
“…In our recent study in 20 adolescents aged 11–19 years with functional abdominal pain disorders (FAPD), we analyzed the effects of PENFS on gastric mechanosensitvity through a water load symptom provocation task (WL-SPT), sleep and psychological functioning, as well as long-term outcomes. [ 62 ] Evoked pain intensity and nausea during WL-SPT were lower following PENFS compared to baseline ( P = 0.004 and P = 0.02 respectively). Self-reported sleep quality, insomnia severity, sleep disturbance, and sleep-related impairment improved after PENFS ( P 's < 0.05) as well as actigraghy-derived sleep onset latency ( P = 0.03).…”
Section: Percutaneous Electrical Nerve Field Stimulationmentioning
confidence: 99%